Analisis Kesulitan Belajar Matematika Pada Siswa MI/SD - Lailatun Nur Kamalia Siregar; Nurma Dayanti; Sri Rahmawati; Rahmah Rahmah; Siti Halisya Parapat; Annisa yulia Nuri; Ade Syahputra (Universitas Palan, 2024)
Student learning disability is a situation where a student is unable to learn as they should. This cannot be ignored and must be addressed immediately by educators, because children's difficulties can become an obstacle in achieving optimal learning goals. The purpose of writing this article is to explore how to identify and overcome learning difficulties in elementary/MI students and to find out the factors that influence these learning difficulties. The research method used is literature study by analyzing several papers/scientific works through hypothesis testing. Based on the results of data analysis, the following results were obtained: a) The types of mathematics learning difficulties faced by elementary/MI students can be divided into two, namely difficulties that are internal to the student and difficulties caused by external factors. student. Ways to overcome this are: 1) Diagnosing students' learning difficulties, 2) Providing supportive mathematics learning advice, 3) Optimizing the implementation of BDR (Learning From Home), and 4) Personal resilience, the idea is to apply the curriculum and utilize blended. learn. b) Factors that cause elementary/MI students' learning difficulties include factors that arise from within the student (internal) and factors that arise from outside the student (external).